2021
DOI: 10.1016/j.bbi.2020.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Lung pathology due to hRSV infection impairs blood–brain barrier permeability enabling astrocyte infection and a long-lasting inflammation in the CNS

Abstract: The human respiratory syncytial virus (hRSV) is the most common infectious agent that affects children before two years of age. hRSV outbreaks cause a significant increase in hospitalizations during the winter season associated with bronchiolitis and pneumonia. Recently, neurologic alterations have been associated with hRSV infection in children, which include seizures, central apnea, and encephalopathy. Also, hRSV RNA has been detected in cerebrospinal fluids (CSF) from patients with neurological symptoms aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 99 publications
0
36
0
Order By: Relevance
“…These cells not only were susceptible to the hRSV infection but also increased levels of IL-6 and TNF-α were detected in the supernatant of N2a hRSV-infected cells [ 151 ]. According to the fact that hRSV infection promotes learning and behavioral impairment and possibly infects neurons, new data showed that hRSV could disrupt the BBB, promoting immune cell infiltration [ 66 ]. Moreover, the behavioral alteration reporter previously in hRSV infected mice can be observed up to 60 days p.i.…”
Section: Neuroinflammation Induced By Respiratory Virusesmentioning
confidence: 99%
See 4 more Smart Citations
“…These cells not only were susceptible to the hRSV infection but also increased levels of IL-6 and TNF-α were detected in the supernatant of N2a hRSV-infected cells [ 151 ]. According to the fact that hRSV infection promotes learning and behavioral impairment and possibly infects neurons, new data showed that hRSV could disrupt the BBB, promoting immune cell infiltration [ 66 ]. Moreover, the behavioral alteration reporter previously in hRSV infected mice can be observed up to 60 days p.i.…”
Section: Neuroinflammation Induced By Respiratory Virusesmentioning
confidence: 99%
“…Moreover, the behavioral alteration reporter previously in hRSV infected mice can be observed up to 60 days p.i. and also increased levels of anti-inflammatory molecules, such as IL-4 and IL-10, and pro-inflammatory molecules including CCL2 were found in the brain of these mice [ 66 ]. Moreover, GFAP was found elevated in hRSV-infected mice′s brains, suggesting that which suggest that are active and possibly causing chronic inflammation [ 66 ].…”
Section: Neuroinflammation Induced By Respiratory Virusesmentioning
confidence: 99%
See 3 more Smart Citations